AL-FARABI’S PHILOSOPHY OF HUMAN PERFECTION AND ITS INTEGRATION INTO MODERN PROFESSIONAL TRAINING - Raximova Iroda (Prospects for innovative technologies in science and education, 2025)
This article explores the philosophical views of Abu Nasr Al-Farabi on human perfection and analyzes how his teachings can be integrated into modern systems of professional training. The study examines Al-Farabi’s concept of the “perfect human” as a holistic individual who embodies intellectual, ethical, and spiritual virtues. Drawing from his ideas on education, knowledge hierarchy, and virtuous society, the article discusses how his legacy offers relevant insights for developing well-rounded specialists in today’s rapidly evolving labor market. A particular focus is placed on aligning competency-based education with Farabian ideals to promote both personal and professional excellence. The study also highlights the importance of moral education, critical thinking, and value-oriented learning in cultivating professionals who are not only technically skilled but also socially responsible and ethically grounded.